What lies beyond the eye: the molecular mechanisms regulating tomato fruit weight and shape - van der Knaap, Esther; Chakrabarti, Manohar; Chu, Yi Hsuan; Clevenger, Josh P.; Illa-Berenguer, Eudald; Huang, Zejun; Keyhaninejad, Neda; Mu, Qi; Sun, Liang; Wang, Yanping; Wu, Shan (Frontiers in Plant Science, 2014)
Domestication of fruit and vegetables resulted in a huge diversity of shapes and sizes of the produce. Selections that took place over thousands of years for alleles that increased fruit weight and altered shape for specific culinary uses provide a wealth of resources to study the molecular bases of this diversity. Tomato (Solanum lycopersicum) evolved from a wild ancestor (S. pimpinellifolium) bearing small and round edible fruit. Molecular genetic studies led to the identification of two genes selected for fruit weight: FW2.2 encoding a member of the Cell Number Regulator family; and FW3.2 encoding a P450 enzyme and the ortholog of KLUH. Four genes were identified that were selected for fruit shape: SUN encoding a member of the IQD family of calmodulin-binding proteins leading to fruit elongation; OVATE encoding a member of the OVATE family proteins involved in transcriptional repression leading to fruit elongation; LC encoding most likely the ortholog of WUSCHEL controlling meristem size and locule number; FAS encoding a member in the YABBY family controlling locule number leading to flat or oxheart shape. For this article, we will provide an overview of the putative function of the known genes, when during floral and fruit development they are hypothesized to act and their potential importance in regulating morphological diversity in other fruit and vegetable crops.